Dynamics of Liver Function among Patients with Malaria in Luanda, Angola: A Cross-Sectional Study - Sebastião, Cruz S.; Cassinela, Edson; Costa-Manuel, Vilma; Matary, Wilma; Nkuku, Maria; Paciência, Isabel; Filipe, Cátia; Cristóvão, Lourenço; Sacomboio, Euclides Nenga Manuel (Archives of Clinical and Biomedical Research, 2025)
Background: Malaria continues a concern in Angola. Liver dysfunction is a relevant feature of malaria. There is no published study exploring liver function dynamics during P.falciparum infection in Angola. Objectives: We investigated the dynamics of liver function among patients with malaria in Luanda, Angola. Methods: This was a cross-sectional study performed with 199 malaria patients, from March-August 2023. Results: About 71% of the patients had low parasitemia, moderate disease (54%), and used Artesunato(39.7%). Decrease in ALT (68.7 to 50.7) was observed from non-severe to severe with increases in AST (56.6 to 134, p<0.05), GGT(51.2 to 99.0), and Bilirubin(0.72 to 1029). We observed higher ALT values in patients using Artimeter, while higher AST and GGT in patients using Artesunate. Higher Bilirubin was observed in patients treated with Coarten. Differences in AST values depending on the antimalarial used were significant(p<0.05). AB blood group presented high AST and GGT values, group B presented high ALT while high Bilirubin was observed in group O. Differences in GGT depending on the blood groups were significant (p<0.05). Elevated ALT, AST, GGT, and Bilirubin were observed in Rh-positive. Conclusions: Several malarian patients could present high AST, ALT, GGT, and Bilirubin values indicating putative liver failure during malaria treatment in Angola.